El Siglo de las Luces di Alejo Carpentier: alla ricerca di un Mondo Migliore, tra lampi rivoluzionari e frammenti di paradiso (Altre Modernità, 2012)
In El siglo de las luces, an apparently historical novel, Alejo Carpentier analyzes the American experience of European modernity through the dislocation of both French Revolution objects and ideas.In this novel, the writer considers the Caribbean (and, so, Latin America) as a paradisiac place coping with theories and ideologies generated in Other centres. Therefore, the Revolution movements towards the suburbs, the intersections of perspectives, visions and translations, organized as a network without a proper centre, lead to a new interpretation of the "American contradistinction" based on accumulation, contradiction and paradox.This article illustrates the challenges to the Revolution paradigm as proposed by Alejo Carpentier, the essential starting point to consider the construction of the “American Being" and the myth of the Promised Land.
Keywords: Cuban narrative; historical fiction; Carpentier; independence; revolution; identity in relation; Glissant